Risks, benefits, and control of information: Two studies of smart electric meter privacy. (8th June 2020) - Rieks, Angela Ramnarine; Dedrick, Jason; Stanton, Jeffrey
Abstract: Smart electric meters collect data on electricity use to potentially improve efficiency for utilities, shape power consumption, and ultimately reduce greenhouse gas emissions. Consumer groups and experts have raised concerns about privacy, as smart meters can provide detailed information about activity within the home. This study examines privacy beliefs of U.S. consumers using qualitative data from focus groups together with experimental data from a national online survey of utility customers. Exploratory analysis of focus group findings suggested that consumers who felt in control of their data perceived fewer risks and more benefits from having access to the data. Participants in the online experiment saw greater risk and less benefit when advised that smart meters could be used to raise prices under time‐of‐use pricing. Participants also saw greater risk when the utility shared customer data with a third party. Risks and benefits influenced perceptions of control. These findings accord with several information privacy frameworks adding new insights about consumers' perceived control over their energy data. The findings can inform utility companies and policymakers with respect to giving consumers more control over their data, reducing consumers' privacy concerns, communicating benefits of smart meter data, and providing accurate information about the risks.